(untitled) (Window of Public Health Journal, 2026)
The World Health Organization reported that more than 1,000 pesticides are used worldwide to prevent pests from damaging food. According to data from the Ministry of Agriculture of the Republic of Indonesia, in 2019, the number of registered and permitted pesticide brands reached 3,207. This study aims to determine the duration of exposure, use of PPE, duration of spraying, and time of pesticide spraying on vegetable farmers in Bonto Lojong Village, Bantaeng Regency. This is quantitative research using descriptive methods. The population in this study comprised all farmers in Bonto Lojong Village, Uluere District, Bantaeng Regency, totaling 136; the sample comprised 42 farmers selected purposively. The results were obtained from questionnaires and analyzed descriptively. The results of the study showed that the number of respondents with long exposure time to farmers was 40 respondents with a percentage of 95.2%, the duration of farmer spraying was not good was 41 respondents with a percentage of 97.6%, the time of farmer spraying was good was 42 respondents with a percentage of 100%, the personal protective equipment of farmers was sufficient was 28 respondents with a percentage of 66.7%.